2013
DOI: 10.1126/scisignal.2003848
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated RasGRP1 Responds to Cytokine Receptor Input in T Cell Leukemogenesis

Abstract: Enhanced signaling by the small guanosine triphosphatase Ras is common in T cell acute lymphoblastic leukemia/lymphoma (T-ALL, but the underlying mechanisms are unclear. Here, we identified the guanine nucleotide exchange factor RasGRP1 (Rasgrp1 in mice) as a Ras activator that contributes to leukemogenesis. We found increased RasGRP1 expression in many pediatric T-ALL patients, which we did not observe in rare early T cell precursor (ETP) T-ALL patients with KRAS and NRAS mutations, such as K-RasG12D. Leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
102
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(108 citation statements)
references
References 76 publications
6
102
0
Order By: Relevance
“…Several groups including our own observed that Ras-PI3K signaling is universally utilized in T-ALL, but with heterogeneous activation patterns. [41][42][43][44][45][46][47] By contrast, the high usage of PI3K-Akt signals is not seen in other hematologic malignancies. 48 Given that PI3K inhibitors like GDC0941 are very potent agents, 49 such inhibition may be useful as therapy for T-ALL, although the heterogeneous activation patterns observed in different T-ALL may complicate a general application.…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…Several groups including our own observed that Ras-PI3K signaling is universally utilized in T-ALL, but with heterogeneous activation patterns. [41][42][43][44][45][46][47] By contrast, the high usage of PI3K-Akt signals is not seen in other hematologic malignancies. 48 Given that PI3K inhibitors like GDC0941 are very potent agents, 49 such inhibition may be useful as therapy for T-ALL, although the heterogeneous activation patterns observed in different T-ALL may complicate a general application.…”
mentioning
confidence: 98%
“…29 Studies with different mouse models and with pediatric T-ALL patient samples pointed to a role for RasGRP1 in T-ALL leukemogenesis. 20,[30][31][32][33] Likewise, the inactivating function of RasGAPs on the Ras pathway also appears critical; combined T cell-specific deletion of NF1 and p120 RasGAPs in mice leads to development of T-ALL 34 and NF1 is mutated in both pediatric and adult T-ALL patients. [35][36][37] In our recent study by Ksionda et al 38 we describe the details of cytokine receptor-Ras pathways in T-ALL and how Ras signals in T-ALL with RasGRP1 overexpression not only differ from those in developing normal T cells (thymocytes) but also from Ras signals in Ras MUT T-ALL.…”
mentioning
confidence: 99%
See 3 more Smart Citations